Pengaruh Aset dan Opini Audit terhadap Tingkat Pengungkapan Laporan Keuangan Pemerintah Daerah di Provinsi Sumatera Selatan - Adelima, Dinna (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
This study aims to determine the effect of assets and audit opinion on the level of disclosure of government financial statements in South Sumatra province in 2019-2021. The population of this study was 13 districts and 4 cities in South Sumatra province and this study used saturated sampling, so that the entire population became the research sample. This research data uses secondary data obtained from the official website of the Audit Board of Republic Indonesia. The analysis model of this study is multiple linear analysis with the help of SPSS program version 25. The results of this study can be concluded that: (1) assets have a significant effect on the level of disclosure of financial statements of district/city governments in South Sumatra province; (2) audit opinions do not have a significant effect on the level of disclosure of financial statements of district/city governments in South Sumatra province; (3) assets and audit opinion simultaneously have a significant effect on the level of disclosure of financial statements of district/city governments in South Sumatra province.